Cultural processes : a social psychological perspective - Leung, Angela K.-y., 1979-; Chiu, Chi-yue, 1963-; Hong, Ying-yi, 1964- (Culture and psychology., 2011)
"This book shows how culturally shared knowledge is used to structure social transactions, and it lays the groundwork for a new science of cultural processes.ûCarol Dweck, Stanford University.